2022
DOI: 10.3389/fnut.2021.809732
|View full text |Cite
|
Sign up to set email alerts
|

Grain-Based Dietary Background Impairs Restoration of Blood Flow and Skeletal Muscle During Hindlimb Ischemia in Comparison With Low-Fat and High-Fat Diets

Abstract: Background: Among vascular pathologies associated with obesity, peripheral artery disease (PAD) occupies the important position. In clinical practice, nutritional interventions are recommended for patients with PAD. In this work, we investigated how the different dietary backgrounds affect the regeneration rate of ischemic hindlimb in mice.Methods: Male C57BL/6J mice were housed on three types of diet: low-fat (LFD), high-fat (HFD), and grain-based diet (GBD) for 13 weeks. Metabolic parameters including FBG le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Further analysis conducted within specific subgroups further strengthens the validity and reliability of these findings. Previous studies have highlighted that malnutrition is linked to an increased risk of CVD and death 15–17. Initially used as a nutritional indicator to predict postoperative morbidity and mortality,18 PNI has been used to measure nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis conducted within specific subgroups further strengthens the validity and reliability of these findings. Previous studies have highlighted that malnutrition is linked to an increased risk of CVD and death 15–17. Initially used as a nutritional indicator to predict postoperative morbidity and mortality,18 PNI has been used to measure nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted that malnutrition Clinical care/Education/Nutrition is linked to an increased risk of CVD and death. [15][16][17] Initially used as a nutritional indicator to predict postoperative morbidity and mortality, 18 PNI has been used to measure nutritional status. Due to the complexity of earlier PNIs in clinical practice, Onodera's calculation method, based on peripheral blood lymphocyte counts and serum ALB levels, became simpler.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a more clinically relevant model although it may take substantial time (8 to 36 weeks) to significantly alter body weight, insulin sensitivity and fasting blood glucose (FBG) level to mimic the corresponding disorder [ 17 , 18 , 19 ]. We used a diet-based mouse model of glucose tolerance impairment described and adopted in published studies [ 20 , 21 , 22 ] and investigated its impact on HGF/VEGF efficacy in mice with hindlimb ischemia to gain insight into systemic metabolic changes and skeletal muscle bioenergetics. Previously our group has demonstrated that HGF/VEGF induced angiogenesis in non-diabetic mice consuming standard grain-based chow [ 8 ].…”
Section: Introductionmentioning
confidence: 99%